Volunteer Programs Supporting People With Dementia/Delirium in Hospital: Systematic Review and Meta-Analysis. (28th May 2020) - Pritchard, Elizabeth; Soh, Sze-Ee; Morello, Renata; Berkovic, Danielle; Blair, Annaliese; Anderson, Katrina; Bateman, Catherine; Moran, Chris; Tsindos, Tess; O'Donnell, Renee; Ayton, Darshini
Abstract: Background and Objectives: Volunteer-delivered programs to assist people with dementia and/or delirium in-hospital can provide person-centered one-on-one support in addition to usual care. These programs could mitigate hospital resource demands; however, their effectiveness is unknown. This review evaluated literature of volunteer programs in acute hospital settings for people living with dementia and/or delirium. Research Design and Methods: Four databases were searched. Studies that reported patient or program outcomes were included (i.e., delirium incidence, length of stay, number of falls, satisfaction). Risk of bias was completed. Meta-analysis was performed where 2 or more studies measured the same outcome. Narrative synthesis was performed on the qualitative results. Results: Eleven studies were included in the review, with varied design, participant groups and outcomes measured. Risk of bias averaged 71%. Volunteer-delivered programs addressed delirium risk factors, for example, hydration/nutrition, mobility, use of sensory aids. Eight patients and 6 program outcomes were captured, but only 3 patient outcomes could be pooled. Meta-analyses demonstrated a reduction in delirium incidence (rate ratio = 0.65; 95% confidence interval [CI] 0.47, 0.90) but no reduction in length of stay (mean difference −1.09; 95% CI −0.58, 2.77) or number of falls (rate ratio = 0.67; 95% CI 0.19, 2.35). Narrative synthesis identified benefits to patients (e.g., less loneliness), volunteers (sense of meaning), and staff (timesaving, safety). Discussion and Implications: Volunteer-delivered programs for inpatients with dementia and/or delirium may provide benefits for patients, volunteers, and staff. However, studies conducted with more robust designs are required to determine overall effectiveness on program outcomes. Further high-quality research appropriate for this vulnerable population is required to identify volunteer program effectiveness.